Analysis Of Combinatorial Aspects Of Random Events - Shingis Maykhanovich Urmanov (Genius Journals, 2024)
This article examines the basic concepts of combinatorics in the context of probability theory. The types of random events and methods for their description using combinatorial approaches are analyzed. Particular attention is paid to the classification of events and methods for calculating their probabilities.
Keywords: Test; event; probability theory